Działania interwencyjne podejmowane podczas kryzysu bankowego w Argentynie w latach 1994-1995 - Ostalecka, Agnieszka (Interventional Activity Taken During the Banking Crisis in Argentina in the Years 1994-1995, 2005)
The article presents the most important interventional activity taken by the Argentinian authorities, which were connected with bringing under control the banking crisis which took place in the years 1994-1995. As a starting point there is described the development of banking crises in division of its main phases are discussed in details and in chronological order. Within the confines of each phase the remedies taken by Argentinian authorities, in particular these taken by the central bank. These actions were in two directions. The first group of used remedies consist in decreasing the shrinking liquidity in the banking system. However, the second group concentrates on restoring confidence to the banking sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 131-141